2015
DOI: 10.11113/jt.v73.4287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Warm Mix Asphalt Performance with High RAP Content

Abstract: The pavement industry is currently forced to find alternative ways to produce asphaltic concrete with the  dwindling supply of new resources and the spiraling cost of materials. Warm Mix Asphalt (WMA) using reclaimed asphalt pavement (RAP) offers a sustainable solution to the problem by reducing energy requirements for production and the reuse of old pavement materials. The effects of warm mix asphalt additive (Sasobit) on mixes containing different percentages of RAP were investigated in the laboratory. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…As shown, the resultant graphs exhibit similar trends with the ITS results whereby the resilient modulus increases with the addition of RAP. This finding is in agreement with the study conducted by Arshad et al on the RAP-WMA mixtures containing 30, 40 and 50% with Sasobit [25]. The addition of RAP produces a stiffer mixture due to aged binder and aggregate.…”
Section: B Optimum Binder Contentsupporting
confidence: 93%
“…As shown, the resultant graphs exhibit similar trends with the ITS results whereby the resilient modulus increases with the addition of RAP. This finding is in agreement with the study conducted by Arshad et al on the RAP-WMA mixtures containing 30, 40 and 50% with Sasobit [25]. The addition of RAP produces a stiffer mixture due to aged binder and aggregate.…”
Section: B Optimum Binder Contentsupporting
confidence: 93%
“…This fly ash can be used directly as the filler. The specific gravity of fly ash was 2.24 g/cm 3 , which is similar to that (2.26 g/cm 3 ) reported in other studies [44]. The fly ash contains particles of an extremely fine size that fill the small gaps in the mixture, thereby increasing the density, stability, and impermeability.…”
Section: The Fly Ash Propertiessupporting
confidence: 86%
“…In all the four mixtures, the density increased with the addition of asphalt and RAP. However, the addition of artificial aggregate decreases the density because the specific gravity of artificial aggregate (2.44 g/cm 3 ) is lower than that of RAP aggregate (2.6 g/cm 3 ). Generally, the specific gravity of artificial aggregate is in the range of 1.33-2.35 g/cm 3 [35], [52].…”
Section: Figure 18 Densitymentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, all the mixes investigated achieved the required minimum TSR of 80%. The results showed that WMA using Sasobit-additive and containing high percentages of RAP could be a sustainable alternative to the conventional HMA mix [13]. Another researcher assessed the moisture sensitivity of WMA containing high RAP content by TSR and MR tests.…”
mentioning
confidence: 99%